2008
DOI: 10.1110/ps.083445408
|View full text |Cite
|
Sign up to set email alerts
|

The C3 domain ofPasteurella multocidatoxin is the minimal domain responsible for activation of Gq‐dependent calcium and mitogenic signaling

Abstract: The large 1285-amino-acid protein toxin from Pasteurella multocida (PMT) is a multifunctional singlechain polypeptide that binds to and enters eukaryotic cells and acts intracellularly to promote G q and G 12/13 protein-dependent calcium and mitogenic signal transduction. Previous studies indicated that the intracellular activity domain responsible for PMT action was located within the C-terminal 600-700 amino acids. In this study, we have exogenously expressed a series of N-and C-terminal PMT fragments direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
(48 reference statements)
2
39
0
Order By: Relevance
“…Similarly, purified TcsLΔ18, although not toxic to cells after microinjection, was able to glucosylate soluble Rac in vitro (23). The toxic activity of PMT was also significantly decreased, but not completely abolished, when the C1 domain was deleted (14,26). We believe that the high amount of RID 2721-3099 -GFP produced in the cell after transfection was sufficient to locate its cellular binding partner, despite not being directly targeted to the plasma membrane.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, purified TcsLΔ18, although not toxic to cells after microinjection, was able to glucosylate soluble Rac in vitro (23). The toxic activity of PMT was also significantly decreased, but not completely abolished, when the C1 domain was deleted (14,26). We believe that the high amount of RID 2721-3099 -GFP produced in the cell after transfection was sufficient to locate its cellular binding partner, despite not being directly targeted to the plasma membrane.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, PMT shares similarity with CNFs in the N-terminal binding and translocation domains. However, the C-terminal catalytic domain of CNFs has no obvious structural similarity with PMT, as evidenced by comparison of the crystal structure of the C-terminal C3 domain of PMT (19), harboring the minimal intracellular activity domain (20), with that of the catalytic domain of CNF1 (33) (Fig. S6 A and B).…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminal fragment of PMT, which consists of 3 domains, covering amino acids 569 to 1285, has been crystallized (19). The structure revealed that the C-terminal C3 domain (residues 1105-1285), which defines the minimal intracellular activity domain responsible for activation of calcium and mitogenic signaling (20), resembles that of a papain-like protease. The domain harbors a catalytic triad characteristic of thiol proteases, consisting of the essential amino acids cysteine-1165 (17,18), histidine-1205 (21) and aspartic acid-1220.…”
mentioning
confidence: 99%
“…Mutation analysis suggested that PMT may be an enzyme toxin with the Cys-His-Asp catalytic triad. More recently, the last 180 amino acids, which encompass the C3 domain, was defined as the minimum domain sufficient to stimulate both calcium-dependent and mitogenic signaling pathways [94] .…”
Section: P Multocida Toxin Pmtmentioning
confidence: 99%